Autoantibody profiles in the sera of European patients with myositis. Issue 2 (1st February 2001) - Brouwer, R; Hengstman, G J D; Egberts, W Vree; Ehrfeld, H; Bozic, B; Ghirardello, A; Grøndal, G; Hietarinta, M; Isenberg, D; Kalden, J R; Lundberg, I; Moutsopoulos, H; et al.
Abstract : OBJECTIVE: To determine the prevalence of myositis specific autoantibodies (MSAs) and several myositis associated autoantibodies (MAAs) in a large group of patients with myositis. METHODS: A total of 417 patients with myositis from 11 European countries (198 patients with polymyositis (PM), 181 with dermatomyositis (DM), and 38 with inclusion body myositis (IBM)) were serologically analysed by immunoblot, enzyme linked immunosorbent assay (ELISA) and/or immunoprecipitation. RESULTS: Autoantibodies were found in 232 sera (56%), including 157 samples (38%) which contained MSAs. The most commonly detected MSA was anti-Jo-1 (18%). Other anti-synthetase, anti-Mi-2, and anti-SRP autoantibodies were found in 3%, 14%, and 5% of the sera, respectively. A relatively high number of anti-Mi-2 positive PM sera were found (9% of PM sera). The most commonly detected MAA was anti-Ro52 (25%). Anti-PM/Scl-100, anti-PM/Scl-75, anti-Mas, anti-Ro60, anti-La, and anti-U1 snRNP autoantibodies were present in 6%, 3%, 2%, 4%, 5%, and 6% of the sera, respectively. Remarkable associations were noticed between anti-Ro52 and anti-Jo-1 autoantibodies and, in a few sera, also between anti-Jo-1 and anti-SRP or anti-Mi-2 autoantibodies. CONCLUSIONS: The incidence of most of the tested autoantibody activities in this large group of European patients is in agreement with similar studies of Japanese and American patients. The relatively high number of PM sera with anti-Mi-2 reactivity may be explained by the use of multiple recombinant fragments spanning the complete antigen. Furthermore, our data show that some sera may contain more than one type of MSA and confirm the strong association of anti-Ro52 with anti-Jo-1 reactivity.